Characterization of roseomonas and nocardioides spp. for arsenic transformation - Bagade, Aditi V.; Bachate, Sachin P.; Dholakia, Bhushan B.; Giri, Ashok P.; Kodam, Kisan M. (Journal of Hazardous Materials, 2016)
The metalloid arsenic predominantly exists in the arsenite [As(III)] and arsenate [As(V)]. These two forms are respectively oxidized and reduced by microbial redox processes. This study was designed to bioprospect arsenic tolerating bacteria from Lonar lake and to characterize their arsenic redoxing ability. Screening of sixty-nine bacterial species isolated from Lonar lake led to identification of three arsenic oxidizing and seven arsenic-reducing species. Arsenite oxidizing isolate Roseomonas sp. L-159a being closely related to Roseomonas cervicalis ATCC 49957 oxidized 2 mM As(III) in 60 h. Gene expression of large and small subunits of arsenite oxidase respectively showed 15- and 17-fold higher expression. Another isolate Nocardioides sp. L-37a formed a clade with Nocardioides ghangwensis JC2055, exhibited normal growth with different carbon sources and pH ranges. It reduced 2 mM As(V) in 36 h and showed constitutive expression of arsenate reductase which increased over 4-fold upon As(V) exposure. Genetic markers related to arsenic transformation were identified and characterized from the two isolates. Moderate resistance against the arsenicals was exhibited by the two isolates in the range of 1-5 mM for As(III) and 1-200 mM for As(V). Altogether we provide multiple evidences to indicate that Roseomonas sp. and Nocardioides sp. exhibited arsenic transformation ability. (C) 2016 Elsevier B.V. All rights reserved.